An in-depth, exploratory assessment of the implementation of the National Health Information System at a district level hospital in Tanzania - Wilms, Miriam Christine; Mbembela, Osman; Prytherch, Helen; Hellmold, Peter; Külker, Rainer (BMC health services research, 2014)
A well functioning Health Information System (HIS) is crucial for effective and efficient health service delivery. In Tanzania there is a national HIS called Mfumo wa Taarifa za Uendeshaji Huduma za Afya (MTUHA). It comprises a guideline/manual, a series of registers for primary data collection and secondary data books where information from the registers is totalled or used for calculations.
Gesehen am 22.09.2020